ON THE ISSUE OF INCREASING THE EFFICIENCY OF FLAT SOLAR COLLECTORS IN HEAT SUPPLY SYSTEMS BY OPTIMIZING THEIR OPERATING PARAMETERS - Исмоилов Маъмуржон Мухторович (European Science Publishing, 2023)
The article discusses the issues of improving the efficiency of solar heat supply systems with flat solar collectors by optimizing their circuit solutions and parameters.
Keywords: solar collector, solar water heating plant, specific flow rate, heating capacity, efficiency.